Theoretical investigation of far-infrared optical behaviors in asymmentrical first-order ferroelectrtric thick film - Mohamad Nazri, Abdul Halif; Khian Hooi, Chew; David R., Tilley; Junaidah, Osman (Universiti Putra Malaysia (UPM), 2009)
Organized by Institute of Advanced Technology (ITMA), Universiti Putra Malaysia, 6th - 8th December 2005 at IOI Marriott, Putrajaya.